Correction: Muck et al. Integrating Fiber Sensing for Spatially Resolved Temperature Measurement in Fuel Cells. Energies 2024, 17, 16 - Nicolas Muck; Christoph David; Torsten Knöri (Energies)
The authors would like to make the following changes to their paper published in Energies [...]